In the shadow of the swastika : the relationships between Indian radical nationalism, Italian fascism and nazism - Casolari, Marzia (Routledge studies in modern history, 2020)
"This book examines and establishes connections between Italian fascism and Hindu nationalism, connections which developed within the frame of Italy's anti-British foreign policy. The most remarkable contacts with the Indian political milieu were established via Bengali nationalist circles. Diplomats and intellectuals played an important role in establishing and cultivating those tie-ups. Tagore's visit to Italy in 1925 and the much more relevant liaison between Subhas Chandra Bose and the INA were results of the Italian propaganda and activities in India. But the most meaningful part of this book is constituted by the connections and influences it establishes between fascism as an ideology and a political system and Marathi Hindu nationalism. While examining fascist political literature and Mussolini's figure and role, Marathi nationalists were deeply impressed and influenced by the political ideology itself, the duce and fascist organisations. These impressions moulded the RSS, a right-wing, Hindu nationalist organisation, and Hindutva ideology, with repercussions on present Indian politics. This is the most original and revealing part of the book, entirely based on unpublished sources, and will prove foundational for scholars of modern Indian history"--